Strategi Pengembangan Objek Wisata Di Kabupaten Pelalawan - Eriyati Eriyati (Pelantar Press, 2023)
Pelalawan Regency is one of the regencies in Riau Province, which has tourism potential that is quite potential to be developed. Tourism objects that need to be developed and have received the attention of the district government since 2015 are the Tajwid Lake and the Petalangan Cultural Center tourist attraction. Lake Tajwid is located in Langgam District and is managed by three parties, firstly the private party manages the rides, secondly the government manages entrance tickets and thirdly Ninik Mamak manages the forest around the lake. The Petalangan Cultural Center tourist attraction is located around the Betung Lake tourist attraction in Betung Village, approximately 16 Km from Pangkalan Kuras sub-district, about 53 Km from Pangkalan Kerinci City of Pelalawan Regency. Betung Village is a village of indigenous Pelalawan residents consisting of the indigenous Malay people of Petalangan which is a miniature of the Petalangan community, this is an attraction for visitors to Lake Betung. The fluctuating number of visitors to tourist attractions from 2012 to 2019, because they have not been supported by facilities and infrastructure as well as supporting infrastructure for tourist objects. In this study, 100 respondents were taken as samples for the Tajwid Lake tourist attraction and 73 respondents for the Petalangan Lake Betung Cultural Center tourist attraction. The sampling technique is accidental sampling. Data analysis for tourism object development strategies uses SWOT, looking at internal factors, namely strengths and weaknesses and external factors, namely opportunities and threats. The results showed that the alternative strategy used for the tourist attraction of Lake Tajwid and the Petalangan Danau Betung Cultural Center is S-O (Strength and Opportunities), has good natural potential to be developed, but has not been used optimally. strategy by using strength (Strength) to take advantage of opportunities (Opportunities).